Implementation and Analysis of Multi-Processing Processor Using Data Encryption Standard on FPGA (International Journal of Engineering and Computer Science, 2017)
: The network communication is mandatory and critical in our day-to-day life. The cryptography is the technique to secure the data in communication field such that privacy of data is maintained. The cryptography has different types of algorithms; they are Data Encryption Standard (DES), Advanced Encryption Standard (AES) and Ron Rivest Adi Shamir & Leonard Adlemen (RSA) Triple Data Encryption Standard algorithm (TDES). The Multi-processor is most used in this era as it is subject to constraints while computing. The Multi-processing is the processing of multiple tasks at a time using two or more central processing units in one system. Here in this paper the Multiprocessing processor and light-weight DES algorithm is implemented using Xilinx 14.7. The simulation is done in Model Sim 6.3 and verifying the code is done by dumping onto Spartan 3 Field programmable gate array (FPGA).